THE EFFECTIVENESS OF THE ELECTRONIC SYSTEM "E-QAROR" - Dadajonov Abdumutalib Karimovich (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, we will discuss the work done in relation to the impact of legislation adopted in our country on the reform process, specifically, resolution 390 of the Cabinet of Ministers on measures to introduce the electronic system "E-qaror" on the activities of local government bodies on June 22, 2021, as well as the development, agreement, adoption, registration, and announcement practices.